Introduksi Teknologi Tepat Guna Mesin Perajang Singkong Sebagai Upaya Peningkatan Usaha UKM Shaqiri Kabupaten Boyolali - Riptanti, Erlyna Wida; Kusnandar, Kusnandar; Harisudin, Mohamad; Setyowati, Nuning; Khomah, Isti; Qonita, Raden Rara Aulia (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance the knowledge and skills of Shaqiri SME workers by introducing appropriate technology, such as cassava chopper machines. The community service activities were carried out with a participatory approach, involving collaboration between the community service team from academia and SMEs as partners. The service team also conducted monitoring and evaluation of the implementation of service activities. The community service team conducted an evaluation using a pre-post intervention approach with evaluation instruments that included sheets and questionnaires, structured interviews, photos, and video documentation. The data was analyzed descriptively and comparatively, focusing on quantitative and qualitative changes. The results showed that the introduction of a cassava chopper machine provided benefits to Shaqiri SMEs in the production process. The cassava chopping process, which previously took a long time, became faster, the thickness of the slices became consistent, and it was less tiring for workers.